Meningkatkan Stimulasi Anak Usia Dini pada Olifant School Yogyakarta melalui Indra Penglihatan dan Peraba - Atmadja, Catharina Kirana; Utomo, Heru Prasetiyo (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
In every child's developmental process, parents must consistently accompany and support them for optimal growth. However, with the changing times, many mothers are now compelled to work outside the home to meet family needs. The phenomenon of mothers working outside the home can have detrimental effects on the family, especially children in their crucial developmental phase from ages 0 to 6. In response to this concern, there is a need for childcare and schools that provide an environment tailored to children's needs, helping to stimulate their brains. Olifant School is an educational and childcare service that focuses on sensory-based child stimulation. This research aims to assess the extent to which the Olifant School building applies architecture and human senses, particularly in the aspects of vision and touch. The method used is library research in the form of literature studies from various sources which are then explained according to existing parameters, which are then analyzed according to existing parameters to draw conclusions. The results of this study indicate that Olifant School in Yogyakarta is one of the structures built based on human senses, specifically vision and touch.